2021
DOI: 10.1109/ojcoms.2021.3093671
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Energy Harvesting-Assisted Overlay Cognitive NOMA Systems With Incremental Relaying

Abstract: In this paper, we analyze the performance of an energy harvesting (EH)-assisted overlay cognitive non-orthogonal multiple access (NOMA) system. The underlying system consists of a primary transmitter-receiver pair accompanied by an energy-constrained secondary transmitter (ST) with its intended receiver. Accordingly, ST employs a time switching (TS) based receiver architecture to harvest energy from radio-frequency signals of the primary transmissions, and thereby uses this energy to relay the primary informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The energy harvested using PS-EH, the relay transmits the signals at the receiver and after employing MRC rule, the signal is utilised for information decoding. Massive MIMO [77], [78], [79], [80], [79], [83], [84] [81], [82], [84] D2D communication [85], [86], [87], [88] [89], [90], [91] [89], cognitive radio [92], [93], [94], [95], [98], [99], [100], [101] [96], [97] multi-user network [102], [103], [104]…”
Section: ) Time Splitting Protocolmentioning
confidence: 99%
“…The energy harvested using PS-EH, the relay transmits the signals at the receiver and after employing MRC rule, the signal is utilised for information decoding. Massive MIMO [77], [78], [79], [80], [79], [83], [84] [81], [82], [84] D2D communication [85], [86], [87], [88] [89], [90], [91] [89], cognitive radio [92], [93], [94], [95], [98], [99], [100], [101] [96], [97] multi-user network [102], [103], [104]…”
Section: ) Time Splitting Protocolmentioning
confidence: 99%
“…Linear energy scavenging overlay networks (LESONs) were investigated extensively. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Nevertheless, few works focused on NLESONs. 16,18,[44][45][46] To be more specific, Solanki et al 16 suggested a system model of NLESONs almost same as Figure 1 but with multiple PDs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Linear energy scavenging overlay networks (LESONs) were investigated extensively 27–43 . Nevertheless, few works focused on NLESONs 16,18,44–46 .…”
Section: Introductionmentioning
confidence: 99%
“…Such work builds upon several foundational studies. These include analyses of throughput for delay-limited and delay-tolerant transmission [12], average error rate and outage probability (OP) for WPC systems with Nakagamim fading channels [26], energy storage effects on OP [27], OP and average throughput of information transfer with Nakagami-m fading channels [28], EH-assisted overlay cognitive non-orthogonal multiple access systems with Nakagami-m fading channels model [29], and OP of RF EH cooperative communication systems over Nakagami-m fading channels [30].…”
Section: Introductionmentioning
confidence: 99%